ECONOMIC ANALYSIS OF COASTAL CARING FARMERS GROUP IN BERAS BASAH VILLAGE, PANGKALAN SUSU DISTRICT, LANGKAT DISTRICT - Asbi Swaka; Tumpal HS Siregar; Zahari Zen (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
"Care for the Coast" Farmers Group is located in Beras Basah Village, Pangkalan Susu District, Langkat Regency, North Sumatra Province, established in 2021 with the approval of the Minister of Environment and Forestry Number 8544/MenLHK-PSKL/PKPS/PSL.0/ 12/2021 Dated 24 December 2021 Concerning the Granting of Approval for Community Forest Management to the Coastal Care Farmers Group covering an area of ​​+ 38 (Thirty Eight) Hectares in the Permanent Production Forest (HP) Area. Currently there is a need for improvements both in terms of Ecotourism so that it develops and the products produced by the group. The objectives of this research are to determine the economic condition of the group, analyze how conditions improve the economy with the use of mangroves as social forests in the Group. The results showed that to carry out promotions, waste handling was further improved. In this case, the government is obliged to assist with road access and safeguard against mangrove encroachment and create innovations both in terms of location aesthetics and the products produced.